Alternative retrofitting strategies to prevent the failure of an under-designed reinforced concrete frame. (July 2018) - Valente, Marco; Milani, Gabriele
Abstract: In Southern European countries several existing reinforced concrete (RC) buildings were designed before the introduction of modern seismic codes and thus they may be potentially vulnerable to horizontal loads. Recent seismic events have also shown that RC buildings designed without specific seismic provisions can be subjected to meaningful damages or even collapse during moderate-to-strong earthquakes. In this framework, straightforward methodologies for a preliminary and suitable seismic assessment and retrofitting of existing RC buildings are required, along with reliable and effective seismic rehabilitation techniques. In this study, a simplified displacement based procedure using non-linear static analyses is applied to obtain a preliminary estimation of the overall inadequacy of an under-designed four-storey RC frame and to propose suitable retrofitting interventions based on different rehabilitation strategies. To this aim, accurate numerical models are developed to simulate the seismic response of the RC frame in the original and retrofitted configurations. The effectiveness of three different retrofitting solutions countering the main structural deficiencies of the RC frame is evaluated through the displacement based approach. Then, non-linear dynamic analyses are carried out to assess and compare the seismic performance of the RC frame in the original and retrofitted configurations. A combined use of different approaches may represent a valuable tool to accurately address the retrofitting interventions and to assess their effectiveness in order to reduce the seismic vulnerability of poorly designed RC buildings. Highlights: Analysis of alternative retrofitting strategies for under-designed RC frames in seismic area Pushover and non-linear dynamic analyses conducted by means of detailed FE approaches Evaluation of strengthening efficiency based on displacement based analysis considerations Discussion on pros and cons of FRP wrapping plus RC jacketing, steel bracing and RC shear walls Comparative considerations on global storey drift reduction and local damage level